The aluminium wire thief : lyrical subject in the poetry collection Metrophobia by the Ukrainian poet Myroslav Laiuk - Helena Frantová (Opera slavica, 2025)
This article presents the work of contemporary Ukrainian poet Myroslav Laiuk (1990). In the texts of his collection Метрофобія (2015) we focus on one aspect — we analyse how the lyrical subject is formed and transformed here, what its role is and what makes it specific. On the material of four selected Laiuk's poems we observe him from a number of angles. On their basis, we can trace the specific character of Laiuk's lyrical subject, which lies in his active creative role, in looking at reality without preconceptions and trying to show it in all its rawness, but also in using a certain degree of playful provocation.